Radiological Parameters Review for Choanal Atresia - Daniela Messineo; Maryia Chernikava; Valeria Pasquali; Serena Bertin; Mario Ciotti; Giulia de Soccio; Vincenzo Savastano; Carlo Catalano (MDPI AG, 2021)
(1) Background: The study aims to identify which imaging parameters are necessary for a new correct surgical approach in the study of choanal atresia, and which anatomical findings are essential for correct planning of endoscopic treatment in choanal atresia. (2) Methods: In this retrospective study, 19 patients with choanal atresia had high-resolution multiplanar imaging (14 cases aged ≤1 year and 5 cases aged 1 to 3 years) and 35 patients in the control group similarly distributed by age. Fourteen variables, the most relevant from a surgical point of view, were selected and measured. A comparison was made between the averages of the study group and the different control groups, either directly observed or selected from the literature, using Pearson's correlation. (3) Results: In 14 out of 26 cases, the differences were statistically significant. There was a correlation between the structures assessed, such as choanal height, rostrum height, and age. (4) Conclusions: Thanks to volumetric reformatting, this work identified and provided the clinician with useful information that helped choose the correct surgical approach. Furthermore, it focused on which imaging parameters are necessary to improve the planning of the surgical correction of choanal atresia.